Valuasi Ekonomi Ekowisata Arboretum Aek Natonang Kecamatan Simanindo Kabupaten Samosir Provinsi Sumatera Utara dengan Pendekatan Travel Cost Method - Devi Fransiska Saragih; Hastanto Bowo Woesono; M. Darul Falah (Jurnal Wana Tropika, 2023)
Aek Natonang Arboretum Ecotourism in Samosir Regency, North Sumatra Province has natural beauty that can be used as a tourist attraction for every visitor. The natural beauty that is owned in reality is not calculated into economic value or market value, so it is important to do economic valuation. By doing this research, it can be known the characteristics of visitors, the amount of economic value of Aek Natonang Arboretum ecotourism based on the travel cost method and find out the factors that influence the intensity of visits. The economic valuation method used is the travel cost method. The travel cost method is applied to estimate the economic value of Aek Natonang Arboretum ecotourism by calculating the cost of travel expenses. Data on travel costs and the number of visits were collected through interviews using questionnaires to visitors within a certain period of time. Then proceed with multiple linear regression analysis to determine the factors that affect the intensity of ecotourism visits to Aek Natonang Arboretum. The results of economic valuation with the travel cost method obtained an average value of Rp238.170,00/visit and the economic value of Aek Natonang Arboretum ecotourism is Rp2.358.359.340,00/year. Factors that influence the intensity of visits are distance, length of travel and travel costs.